Edukasi Penurunan Nyeri Pinggang Bawah Pada Ibu Hamil Trimester III Di Kecamatan Labuhan Deli Kabupaten Deli Serdang - Selamat Tuahta Sipayung (STIKES Columbia Asia Medan, 2023)
This study aims to provide education on reducing lower back pain in pregnant women in the third trimester in Labuhan Deli District, Deli Serdang Regency. Community service methods were conducted through counseling and training for pregnant women in the third trimester at several predetermined locations. Education focused on understanding the causes of lower back pain during pregnancy, daily prevention techniques, and safe and effective physical exercises to reduce pain. After the training, an evaluation was conducted to measure the increase in knowledge and skills of pregnant women in managing lower back pain. The results showed an increase in knowledge and skills of pregnant women in managing lower back pain after receiving education. Through this approach, it is expected to improve the well-being of pregnant women and reduce complaints of lower back pain during the third trimester of pregnancy in Labuhan Deli District, Deli Serdang Regency.